Immediate and differed effects of various training loads over the responses of the autonomic nervous system. A case study on two olympic female swimmers - Hellard, P.; Lacoste, L.; Barale, F.; Rey, J. L.; Schmidt, L.; Fouillot, J. P. (First international symposium sciences and practices in swimming, 2006)
This study aims at assessing the immediate and differed effects of training loads on the RR variability of heart rate frequency for two female swimmers, who were Olympic medalists in Athens 2004. The various indicators of RR variability were correlated with a training session performed during a given a week (S0), a week before (S-1), and two weeks before (S2). The effects of the training loads (i.e. low intensity (Ll) (under the onset of the blood lactate accumulation), high intensity (HI), competition ratio LI/H1, general physical preparation (GC), maximal strength (MS) and strength endurance (SE) are different for each swimmer and for each given period of time. For swimmer #1, HI was associated to an increased energy level in the autonomic nervous System (ANS) in the middle and long-term; however, SE was correlated to a decrease of its various components (p < 0.05). For swimmer #2, the predominance of low intensity training was linked to an amplification of the energy indicators of the ANS a week later.